Avaliação de indutores hormonais na reprodução de machos da espécie Leiarius marmoratus (GILL, 1870) - Araújo, João Ênio Xavier Souza (2012)
A espécie jundiá amazônico (Leiarius marmoratus) é proveniente da bacia amazônica e tem hábito alimentar onívoro. Jundia amazon (Leiarius marmoratus) is from the Amazon basin and with amnivorous feeding habitat. This species has been used in some Brazilian states for the creation of hybrid fish by crossbreeding with Pseudoplatystoma spp females. The objective of this study was to evaluate the efficiency of male spawning induction in the Amazon catfish using different hormone inducers, and to investigate qualitative and quantitative semen characteristics. Spawning was induced with carp pituitary extract (CPE) and Ovopel (synthetic product). Four treatments (three Ovopel doses and one CPE dose) consisting of four replicates were evaluated: 0.2, 0.4 and 0.6 Ovopel pellet/kg live weight, and 2.5 mg CPE/kg live weight. No significant difference in sperm volume, motility and vigor, time of motility, sperm concentration or normal and abnormal spermatozoa was observed between treatments. There was also no significant difference in terms of primary or secondary sperm pathologies, except for the secondary sperm abnormality of loose heads which was significantly less frequent in the treatments using 0.4 and 0.6 Ovopel pellet/kg live weight. In conclusion, this study demonstrates that Ovopel can replace CPE for the induction of male spawning in L. marmoratus.